Anatomical Variations of Sphenoid Sinus Pneumatisation in Vojvodina’s Population - Vlaški, Angelina; Erić, Mirela; Sotirović Seničar, Slavica (Medicinski podmladak, 2019)
Introduction: The sphenoid sinus is considered to be morphologically one of the most variable structures in the human body. Aim: The aim of this study was to analyse the variants of pneumatisation of sphenoid bone and to determine differences in relation to the gender and body side in the population of Vojvodina. Material and methods: This retrospective study included 60 patients (30 males and 30 females), mean age 39.92 years, who underwent a CT scan of paranasal sinuses in the Center of Radiology, Clinical Center of Vojvodina, Novi Sad. The total number of analysed sinuses was 120. The CT scan images were presented in coronal, sagittal and axial planes. The types and the extensions of sinus were analysed. Results: The most common type of the sphenoid sinus was sellar (83.33%), followed by presellar (15.83%). The conchal type was found in only one case (0.83%). The most frequent subtype of the posterior extension in males was subdorsal (48%) and in females subtype body (42%). The presence of both lateral and anterior extensions was found in 18.33% cases, only lateral extension in 45% cases and only anterior in 10%. Conclusion: The most common type of sphenoid sinus was sellar, while the conchal type was the rarest one. The most frequent subtype was subdorsal in males and subtype body in females. The lateral extension was observed more often in comparison to the anterior extension. Keywords: sphenoid sinus, pneumatisation, extensions